2002
DOI: 10.1034/j.1600-0404.2002.01086.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparing two programs of cognitive training in Alzheimer's disease: a pilot study

Abstract: Both AD groups showed a substantial improvement after training in a direct performance measure of everyday functioning. However, results at neuropsychological tests suggest that training activities of daily living (supported by procedural memory) may be more effective than stimulating "residual" cognitive functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
3
5

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(83 citation statements)
references
References 37 publications
5
70
3
5
Order By: Relevance
“…Similarly, results from Farina et al (2002) provide further support for the stimulation of procedural memory. In their first study, the authors compared the stimulation of procedural memory with the training of partially spared cognitive functions.…”
Section: Frontiers In Human Neurosciencementioning
confidence: 54%
See 1 more Smart Citation
“…Similarly, results from Farina et al (2002) provide further support for the stimulation of procedural memory. In their first study, the authors compared the stimulation of procedural memory with the training of partially spared cognitive functions.…”
Section: Frontiers In Human Neurosciencementioning
confidence: 54%
“…In their first study, the authors compared the stimulation of procedural memory with the training of partially spared cognitive functions. Their findings demonstrated that both training exercises induced a substantial improvement in everyday functioning, even if the results of cognitive tests suggested that the training of procedural memory may have been more effective (Farina et al, 2002). In a subsequent study, Farina et al (2006) compared the effect of recreational activities with gains induced by specific cognitive programs (i.e., procedural memory training vs. neuropsychological rehabilitation of "residual functions").…”
Section: Frontiers In Human Neurosciencementioning
confidence: 99%
“…Farina et al (2002) compararam dois tratamentos em que um estimulava a memória procedural com treino em AVD e o outro realizava treinos específicos de função cognitiva como memória, atenção e linguagem, e concluíram que ambos os grupos apresentaram melhora na performance em AVD, embora as teses neuropsicológicas tivessem sugerido que o treino de AVD é mais eficaz que a estimulação das funções cognitivas deficitárias.…”
Section: Introductionunclassified
“…Skills Assessment [78], ECog [79], self-rating inventory for daily function [82]. A common theme discussed in all papers identi ed was that even though there were cognitive improvements they tended not to translate into detectable improvements in daily functioning…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%